#TITLE_ALTERNATIVE# - DJAILANI (NIM 12204017); Pembimbing: Ir. Tutuka Ariadji, MSc, Ph.D., IKHWANUSHAFA
Plan of Development is very important to be conducted in oil industry, where a lot of money needed for producing an oil field. Reservoir simulation is an indispensable tool for planning the development of a reliable field for predicting realistic reservoir performance. X Field is an oil field with a complex carbonate reservoir. Amount of oil that produced from the field was very limited, it was just 2,23 % from just one well. These studies require field development by adding a few wells in a potential area. Simulation with different scenarios results in 14,02 % Recovery Factor of 3 producing wells. After simulation process, the next step is to analize economic aspect of the development scenario which is offered by reservoir simulation, and by using some capital and non capital cost assumptions we obtaine some economic indicator results, NPV Value for Government is 50,627 MUS$, NPV Value for Contractor is 8,346 MUS$, ROR is 75,6 %, POT is after 2,98 years and PI value is about 1,76.